2016
DOI: 10.1248/bpb.b16-00461
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rac1/WAVE2 Signaling in Mediating the Inhibitory Effects of γ-Tocotrienol on Mammary Cancer Cell Migration and Invasion

Abstract: The majority of breast cancer deaths result from the progression of this disease to a metastatic phenotype. Rac1 and Cdc42 are Rho family members that together with their downstream effectors, Wiskott-Aldrich Syndrome protein-family verprolin-homologous protein 2 (WAVE2) and Arp2/3, play an important role in cytoskeletal reorganization and the formation of membrane protrusions that promote cancer cell migration and invasion. γ-Tocotrienol, is a natural isoform within the vitamin E family of compounds that inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…147 Other properties of cancer cells such as cell migration, cell invasion, and epithelial-mesenchymal transition have also been reported to be inhibited by tocotrienols in lung cancer cells, gastric cancer cells, and breast cancer cells in vitro, in cell migration assay, wound healing assay, and cell invasive assay. 119,123,153 In γ-T3-treated breast cancer MDA-MB-231 cells, cell migration machinery regulators such as RAC1 and WAVE2 signaling were reduced. 153 In addition to the reduced cell migration, γ-T3-treated breast cancer MDA-MB-231 and T-47D cells showed epithelial-mesenchymal transition.…”
Section: Suppression Of Stemness and Inhibition Of Cell Migration/imentioning
confidence: 99%
See 1 more Smart Citation
“…147 Other properties of cancer cells such as cell migration, cell invasion, and epithelial-mesenchymal transition have also been reported to be inhibited by tocotrienols in lung cancer cells, gastric cancer cells, and breast cancer cells in vitro, in cell migration assay, wound healing assay, and cell invasive assay. 119,123,153 In γ-T3-treated breast cancer MDA-MB-231 cells, cell migration machinery regulators such as RAC1 and WAVE2 signaling were reduced. 153 In addition to the reduced cell migration, γ-T3-treated breast cancer MDA-MB-231 and T-47D cells showed epithelial-mesenchymal transition.…”
Section: Suppression Of Stemness and Inhibition Of Cell Migration/imentioning
confidence: 99%
“…119,123,153 In γ-T3-treated breast cancer MDA-MB-231 cells, cell migration machinery regulators such as RAC1 and WAVE2 signaling were reduced. 153 In addition to the reduced cell migration, γ-T3-treated breast cancer MDA-MB-231 and T-47D cells showed epithelial-mesenchymal transition. 119 Using the same in vitro assays, δ-T3 was also found to suppress the migration and invasion of non-small lung cancer cells 124 and colon cancer cells.…”
Section: Suppression Of Stemness and Inhibition Of Cell Migration/imentioning
confidence: 99%
“…The authors deciphered that γT3 caused significant reductions in cell invasion and migration. The suppression of Ras-related C3 botulinum toxin substrate 1 (Rac1)/Wiskott-Aldrich Syndrome protein-family verprolin-homologous protein 2 (WAVE2) signaling was proposed as the possible underlying mechanism (characterized by reduced expression of WAVE2, Arp2, Arp3, and reduced phosphorylation of Rac1/Cdc42) [395]. All these signaling molecules are essential for cytoskeletal reorganization, formation of membrane protrusions and raffles that promote cancer cell mobility [396].…”
Section: Effects Of Tocotrienol On Cancersmentioning
confidence: 99%
“…Interestingly, numerous studies have shown that tocotrienols, but not tocopherols, have selective antiproliferative and apoptotic effects against various forms of breast cancer, while have little effect on normal mammary epithelial cell growth or function [14,15,25]. The anticancer Corn 112 ---0…”
Section: Vitamin E and Breast Cancermentioning
confidence: 99%